Об’єднанi (p, q; a, y, l)-деформацiї осциляторних та гiбридних осциляторних алгебр i двовимiрної конформної теорiї поля - Burban, I. M. (Publishing house "Academperiodika", 2018)
The unified multiparametric generalizations of the well-known two-parameter deformed oscillator and hybrid oscillator algebras are introduced. The basic versions of these deformations are obtained by imputing the new free parameters in the structure functions and by a generalization of defining relations of these algebras. The generalized Jordan–Schwinger and Holstein–Primakoff realizations of the U^aypq (su(2)) algebra by the creations and annihilations operators of the basic versions of these deformations are found. The (p, q; a, y, l)-deformation of the two-dimensional conformal field theory is considered. The pole structure of the (p, q; a, y, l)-deformed operator product expansion (OPE) of the holomorphic component of the energy-momentum tensor with primary fields is found. The two-point correlation function of the (p, q; a, y, l)-deformed two-dimensional conformal field theory is calculated.